2019
DOI: 10.3390/toxins11120690
|View full text |Cite
|
Sign up to set email alerts
|

Species Composition and Toxigenic Potential of Fusarium Isolates Causing Fruit Rot of Sweet Pepper in China

Abstract: Apart from causing serious yield losses, various kinds of mycotoxins may be accumulated in plant tissues infected by Fusarium strains. Fusarium mycotoxin contamination is one of the most important concerns in the food safety field nowadays. However, limited information on the causal agents, etiology, and mycotoxin production of this disease is available on pepper in China. This research was conducted to identify the Fusarium species causing pepper fruit rot and analyze their toxigenic potential in China. Forty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…This study confirmed the susceptibility of peppers to mycotoxin contamination (Gambacorta et al, 2018). The study of Wang et al, (2019) confirmed the susceptibility of peppers to mycotoxin contamination. Furthermore, diffusions of some mycotoxins from lesions into the surrounding sound tissues were observed in sweet peppers, implying migration from colonized to non-colonized parts of pepper tissues, which implied the risk of mycotoxin contamination in non-infected parts of food product.…”
Section: Introductionsupporting
confidence: 79%
“…This study confirmed the susceptibility of peppers to mycotoxin contamination (Gambacorta et al, 2018). The study of Wang et al, (2019) confirmed the susceptibility of peppers to mycotoxin contamination. Furthermore, diffusions of some mycotoxins from lesions into the surrounding sound tissues were observed in sweet peppers, implying migration from colonized to non-colonized parts of pepper tissues, which implied the risk of mycotoxin contamination in non-infected parts of food product.…”
Section: Introductionsupporting
confidence: 79%
“…According to Farr and Rossman (2022), more than 400 diseases caused by this species have been reported on various host plant species in different countries, including pepper. Internal fruit rot of chilli pepper was previously reported to be caused by members of F. incarnatum , F. incarnatum‐equiseti species complex (FIESC), F. lactis species complex (FLASC), F. oxysporum , F. proliferatum , F. equiseti , F. solani, F. fujikuroi , F. subglutinans and F. concentricum in several countries (Frans et al, 2017; Mathur & Utkhede, 2004; Poucke et al, 2012; Ramdial et al, 2016, 2017; Tariq et al, 2018; Wang et al, 2013; Wang, Wang, et al, 2019; Yang et al, 2010; Zhu et al, 2021). According to the checklist of Fusarium species reported from Turkey, F. incarnatum has been reported previously from different host plants such as protea ( Protea cynaroides L.), wheat, corn and kiwifruits (Asan, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have focused their attention on cereals, while neglecting other crops. A paper from a Chinese group reports on the identification of the Fusarium species causing sweet pepper fruit rot and on the kinds of mycotoxins produced by these microorganisms [ 3 ].…”
mentioning
confidence: 99%